2011
DOI: 10.1159/000335070
|View full text |Cite
|
Sign up to set email alerts
|

Living Donor Kidney Donation: Another Form of White Coat Effect

Abstract: Background/Aims: Living donor nephrectomy can be associated with increases in blood pressure several years following the procedure, but the best method to assess blood pressure during the living donor evaluation process is unclear. Methods: Living kidney donors underwent casual clinic and ambulatory blood pressure monitoring (ABPM) and measurement of central aortic pressures at baseline and 6 months following donor nephrectomy. Results: There was a significant decline in clinic systolic blood pressure (SBP; p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Markers of endothelial function and bone metabolism demonstrated significant changes related to the decline in GFR while the inflammatory markers showed no significant changes. Mean DBP remained unchanged, while mean SBP was significantly lower at 6 months post donation as we reported previously [10]. The changes in eGFR we observed are similar to those recently reported by Kasiske et al 6 months post-donation [17].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Markers of endothelial function and bone metabolism demonstrated significant changes related to the decline in GFR while the inflammatory markers showed no significant changes. Mean DBP remained unchanged, while mean SBP was significantly lower at 6 months post donation as we reported previously [10]. The changes in eGFR we observed are similar to those recently reported by Kasiske et al 6 months post-donation [17].…”
Section: Discussionsupporting
confidence: 90%
“…With long term follow-up, living kidney donors have shown loss of circadian blood pressure rhythm on ambulatory blood pressure monitoring despite maintaining normotensive status [9]. However, when this loss of circadian rhythm occurs is not precisely established and our recent data found no significant changes in blood pressure and the blood pressure circadian rhythm at 6 months post donation by ambulatory blood pressure monitoring (ABPM) [10]. …”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, hypertensive blood pressure readings without confirmation by 24 h blood pressure recording may reflect white coat hypertension. 30 31 In our study, all new diagnoses of hypertension had to be verified by 24 h ambulatory blood pressure recording. Blood pressure values in the normal range were only accepted as ‘normal’ if a list of drugs taken the same day was reported to SOL-DHR.…”
Section: Discussionmentioning
confidence: 99%
“…A recent small study of 17 donors showed remarkable differences between clinic systolic blood pressure and ambulatory systolic blood pressure prior to donation. These differences disappeared 6 months after donation, suggesting a substantial white-coat effect on systolic blood pressure associated with living kidney donor evaluation (44).…”
Section: Hypertensionmentioning
confidence: 98%